a) 9x – 3 = 2x + 5
b) 7x + 8 = x + 20
c) 3( x + 5 ) = 9
d) 4 (2x – 3 ) = 0
e) 4( x -4) = 3x + 1
f) 6(5-2x) = 5(3x + 2)


Odpowiedź :

Odpowiedź:

A)

9x – 3 = 2x + 5

9x - 2x = 5 + 3

7x = 8      /:7

x = 8/7 = 1 1/7

b)

7x + 8 = x + 20

7x - x = 20 - 8

6x = 12     /:6

x = 2

c)

3( x + 5 ) = 9

3x + 15 = 9

3x = 9 - 15       /:3

x = -6/3 = -2

d)

4 (2x – 3 ) = 0

8x - 12 = 0

8x = 12      /:8

x = 12/8 = 1 4/8 = 1 1/2

e)

4( x -4) = 3x + 1

4x - 16 = 3x + 1

4x - 3x = 1 + 16

x = 17

f)

6(5-2x) = 5(3x + 2)

30 - 12x = 15x + 10

-12x - 15x = 10 - 30

-27x = -20        /:(-27)

x = 20/27

Szczegółowe wyjaśnienie: